Do assistencialismo à luta por direitos: as pessoas com deficiência e sua atuação no processo de construção do texto constitucional de 1988 - Almeida, Késia Pontes de (2019)
This research aims to think about the performance of people with disabilities in the construction of constitutional text of 1988, through its representatives in the Magna Carta audiences held in the Black, Native, Disabled People and Minorities Subcommittee that composed the Social Order Committee works with two other groups. Based on the Welfarism axis oriented towards the struggle for rights, this text was divided into three parts. In chapter 1, we recover the historical journey and present some national and international landmarks on the policies regarding people with disabilities, besides the paradigm shift of the social context based on a segregationist model for the implantation of integration policies of these individuals, mainly in the decades of 1970 and 1980. We also highlighted relevant points about the constitution of social movements of people with disabilities and the participation of civil society, according to the Gramscian sense, in which we emphasize the institutions structurally constituted several decades before this period and that intended to provide services. We focused on concepts to understand the axis that shows hegemonies and counter-hegemonies in the process of fighting philanthropy and establishing rights, such as: i) relationship between State and civil society; (ii) exclusion; and iii) citizenship, with emphasis on the broad movement in the mentioned decades, which allowed the participation in the constitutional text. The chapter 2 dealt with reports of leaderships, through oral interviews (BRASIL/SDH, 2010), with the purpose of listing issues related to the insertion of people with disabilities, reflecting on their contact with the political movement for rights and to verify how their militancy was developed until the Constitution of 1987. We established a panorama of who these individuals are, what their family origins are and to which groups or social classes are linked to relate them as subjects and to determine the representative factors that characterize the struggle for citizenship and against philanthropy. In turn, chapter 3 refers to the statements cited in the meeting minutes of Social Order Committee and the Black, Native, Disabled People and Minorities Subcommittee. We reinforced the problems related to people with intellectual, hearing, physical and visual disabilities, highlighting the specificities of each one, the tensions and heterogeneities that formed the audiences, to understand the contradictions of various social movements by rights. In the conclusion, we recover important elements described in item 3, with the purpose of discussing on the representatives participation in the constituent text. Subsequently, we talk about the memory built by organs linked to State, in combination with part of society, on the development of the struggle for rights of people with disabilities. Finally, we pointed out the deployments of the Constitution and showed how the guarantee of rights continued from the 1990s, whether in civil society or in the political sphere.